“Undesirables Entering the Town to Look for Good Times”: Banff Confronts Its Counterculture Youth Scene, 1965–1971 - Bradley, Ben (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2018)
Small urban centres remain largely overlooked in historical studies of the counterculture in Canada. This article examines the rise and fall of the scene in Banff, Alberta—a single-industry town with an economy based on accommodating travelling pleasure-seekers, that lacked an elected municipal government. Beginning in 1965, a fast-growing number of counterculture and transient youths trekked to Banff each summer. Some used its public spaces for behaviour Banffites deemed inappropriate and also bothersome to tourists, which pushed officials, business owners, and other permanent residents to debate the nature and limits of tolerance in their community. A few facilities and services welcomed counterculture youth, but most residents remained apprehensive about how Banff’s image might be affected during the high tourist season. After years of mounting frustration and resentment, tensions reached a crescendo in 1971, following which Banff’s status as a counterculture destination abruptly collapsed.